Social correlates of sexual risk behaviors among urban men who have sex with men in Kolkata, India (South East Asia Journal of Public Health, 2015)
The factors defining the vulnerability of men who have sex with men (MSM) population are multiple and follow a complex social pattern culminating to their risk for human immunodeficiency virus (HIV) transmission. Even though the vulnerability of this population has been previously reported, prevention efforts are poor, may be due to the lack of understanding of the nature of sexual behavior in its social context. The main aim of this research was to study the social factors that are correlated with sexual risk behavior among the urban MSM population living in Kolkata. A community-based cross-sectional survey was conducted in the Kolkata Metropolitan Area using a pre-structured interview guide. Data obtained from 126 beneficiaries of the NGO networks representing the MSMs of the area, were analyzed. Prevalence of sexually transmitted infections (STI) among the MSMs during a recall period of last six months was used as a marker of sexual risk. Multiple logistic regression analyses were done to estimate and test associations between STI and social variables. The prevalence of STI among the respondents was 60.3% (95% confidence interval (CI): 51.2-68.9). Inconsistent condom use (OR:11.98; 95%CI: 4.03-35.59), low self-esteem (Rosenberg scale) (OR:4.18; 95%CI: 1.48-11.82), substance abuse during sexual activity (OR:4.94; 95%CI: 1.30-18.82), and adverse reactions when coming out (OR:4.91; 95%CI: 1.63-14.77) were significantly associated with STI prevalence. For HIV risk reduction among the MSM population, intervention efforts should address the potential social stressors and adverse life events in addition to condom promotion.DOI: http://dx.doi.org/10.3329/seajph.v4i1.21834 South East Asia Journal of Public Health Vol.4(1) 2014: 17-24